The Social Impact of Digital Youth Work: What Are We Looking For? - Pawluczuk, Alicja (2019)
Digital youth work is an emerging field of research and practice which seeks to investigate and support youth-centred digital literacy initiatives. Whilst digital youth work projects have become prominent in Europe in recent years, it has also become increasingly difficult to examine, capture, and understand their social impact. Currently, there is limited understanding of and research on how to measure the social impact of collaborative digital literacy youth projects. This article presents empirical research which explores the ways digital youth workers perceive and evaluate the social impact of their work. Twenty semi-structured interviews were carried out in Scotland, United Kingdom, in 2017. All data were coded in NVivo 10 and analysed using thematic data analysis (Braun & Clarke, 2006). Two problems were identified in this study: (1) limited critical engagement with the social impact evaluation process of digital youth work projects and its outcomes, and (2) lack of consistent definition of the evaluation process to measure the social impact/value of digital youth work. Results of the study are examined within a wider scholarly discourse on the evaluation of youth digital participation, digital literacy, and social impact. It is argued that to progressively work towards a deeper understanding of the social value (positive and negative) of digital youth engagement and their digital literacy needs, further research and youth worker evaluation training are required. Recommendations towards these future changes in practice are also addressed.